IMPLEMENTASI PENGELOLAAN BADAN USAHA MILIK DESA DI DESA RAE KECAMATAN BEO UTARA KABUPATEN KEPULAUAN TALAUD - MAILANTANG, YULASTRI; LALOMA, ALDEN; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2019)
The implementation of management of village-owned companies must touch the community through the utilization of existing potential in the village with the aim of improving the economy of the local village community. The purpose of this study was to determine the implementation of management of village-owned enterprises in the rae village of north beo district talaud island regency. This study uses descriptive qualitative research methods. Data collection techniques used were interviews, documentation and data collection with documents to see how the implementation of management of village-owned enterprises in the rae village of north beo district talaud island regency. The researcher used four indicators, namely: planning, organizing, actuating and controlling. Based on the results of this study it was stated that the implementation of management of village-owned enterprises in the rae village of north beo district talaud island regency had not been effective and efficient, because the planned program has not been in accordance with the needs of the village community in general, organizing that is not in accordance with the needs of the business entity, actuating carried out in the conduct of business activities is not maximum, and controlling was not optimal. Thus It can be concluded that the achievement of the objektives of implementation of management of village-owned enterprises in the rae village of north beo district talaud island regency it was not effetive and efficient.Keywords: Implementation, Management, Of Village, Business Entities.